Wanprestasi Dalam Perjanjian Kredit Transaksi Pinjaman Online Pay Later Pada Aplikasi Shopee - A, Amelia; Delyananda, Zahrah Rani’ah; Tanjung, Salsas Bila Juniyanti; Faisal, Adhiya; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this paper is to examine and find out what form of default in online credit agreements with the pay later method on the Shopee application and also to find out the efforts to resolve default disputes by Shopee Pay Later users in online credit agreements on the Shopee application. The research method used in this study is normative research with a case study method, which is an in-depth qualitative research method about a case or phenomenon. The results of the study show that the mechanism for using the Shopee Pay Later feature is very easy and simple because users only need to carry out the activation process through the Shopee application. Shopee does not use litigation or non-litigation processes to resolve this problem, users of the Shopee Pay Later feature will not experience legal consequences if they default. In this case, Shopee can freeze the user's account, reduce the user's Shopee Pay Later limit, record late payments on the OJK Financial Information Services System (SLIK), and take other legal actions